AB0073 Accumulation of advanced glycation end products (AGES) in osteoarthritic cartilage is related to an impairment of the adaptative mechanism of GLYOXALASE-1. (15th June 2017) - Trellu, S; Courties, A; Jaisson, S; Friguet, B; Houard, X; Ehkirch, F-P; Jacques, C; Berenbaum, F; Sellam, J
Abstract : Background: Advanced glycation end-products (AGEs) that result from a non-enzymatic reaction between a sugar and a protein, are generated during tissular ageing. Accumulation of AGEs could also be part of the osteoarthritis (OA) process by modifying the biomechanic properties of cartilage and by inducing chondrocyte activation. Glyoxalase-1 (Glo-1) is the main enzyme involved in the removal of AGEs precursors, especially the AGE carboxymethyllysine (CML). Objectives: We aimed to quantify CML in human osteoarthritic cartilage, to investigate Glo-1 expression in chondrocytes and to study chondrocytic Glo-1 regulation in an inflammatory context. Methods: 1) Ex vivo: Osteoarthritic cartilages from patients undergoing knee replacement were collected, dissected and incubated for 24h with or without IL-1β (5ng/ml). We quantified CML in these cartilage explants using liquid chromatography and mass spectrometry, Glo-1 protein expression (Western Blot and immunohistochemistry) and Glo-1 enzymatic activity by measuring the kinetic of formation of the Glo-1 product (S-D lactoylglutathione) using spectrophotometry at 240nm during 10 minutes. 2) In vitro: Primary cultured murine chondrocytes (C57B6) were stimulated 72 h with increasing IL-1β doses (0 to 10ng/mL). Glo-1 expression was assessed by quantitative RT-PCR, Western blot and enzymatic activity. To analyze whether oxidative stress is involved in Glo-1 regulation induced by IL-1β, cells were treated with inhibitors of mitochondrial oxidative stress (MitoTEMPO) or of nitric oxide (NO) synthase (L-NAME). Results: 1) Ex vivo, CML was found in all human OA cartilage samples and its level increased according to age (correlation coefficient CML/age: r=0.78, p<0.01). In parallel to CML increase, Glo-1 protein was expressed in chondrocytes on all layers of cartilage. A positive correlation was found between Glo-1 enzymatic activity and the age of the patients (r=0.45, p<0.05) but was lost in case of incubation with IL-1β (r=-0.09, p non significant). 2) In vitro, in murine chondrocytes cultures, we observed a dose-dependent decrease of IL1β-induced Glo-1 mRNA (0.67 fold, p<0.05), protein quantity (0.56 fold, p<0.05) and enzymatic activity (0.7 fold, p<0.05) (n=5). The blockade of NO by L-NAME, and of mitochondrial oxidative stress by MitoTEMPO counteracted the downregulation of IL1β-induced Glo-1 expression and enzymatic activity (n=5). Conclusions: We show here that the age-dependent accumulation of AGEs in OA cartilage could be due to an impairment of the adaptative mechanism of Glo-1, mediated by oxidative stress. Further studies aiming at targeting Glo-1 restauration as a therapeutical strategy for ageing-related OA are needed. Disclosure of Interest: None declared